2016
DOI: 10.3892/br.2016.733
|View full text |Cite
|
Sign up to set email alerts
|

Effects of diammonium glycyrrhizinate on random skin flap survival in rats: An experimental study

Abstract: Abstract. Partial necrosis of skin flaps continues to restrict the survival of local skin flaps following plastic and reconstructive surgeries. The aim of the present study was to investigate the effects of diammonium glycyrrhizinate (DG), a salt of glycyrrhetinic acid that has been widely used in the therapy of chronic hepatitis and human immunodeficiency virus infection, on random skin flap survival in rats. McFarlane flaps were established in 60 male Sprague-Dawley rats randomly divided into three groups. G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…[6][7][8][9][10][11][12] The evaluation of the results of interventions performed in experimental models of skin grafts and flaps include some methods, such as gene expression analysis, 10,13 protein expression analysis, 11,12,[14][15][16] assessment of histological changes, 11,12,15 and the percentage of viable tissue. 6,7,17,18 The latter is widely used for being fast, inexpensive, and efficient. Three methods can be used to evaluate the percentage of viable tissue: weight of paper template (WPT), 17,18 paper template area (PTA), 19 and photographic area (PA).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[6][7][8][9][10][11][12] The evaluation of the results of interventions performed in experimental models of skin grafts and flaps include some methods, such as gene expression analysis, 10,13 protein expression analysis, 11,12,[14][15][16] assessment of histological changes, 11,12,15 and the percentage of viable tissue. 6,7,17,18 The latter is widely used for being fast, inexpensive, and efficient. Three methods can be used to evaluate the percentage of viable tissue: weight of paper template (WPT), 17,18 paper template area (PTA), 19 and photographic area (PA).…”
Section: Introductionmentioning
confidence: 99%
“…6,7,17,18 The latter is widely used for being fast, inexpensive, and efficient. Three methods can be used to evaluate the percentage of viable tissue: weight of paper template (WPT), 17,18 paper template area (PTA), 19 and photographic area (PA). 11,14,16 The paper template method was first described by Sasaki and Pang in 1980 20 and since then it has been used to evaluate the percentage of flap necrosis on the seventh postoperative day.…”
Section: Introductionmentioning
confidence: 99%
“…Besides the use of iron chelation, superoxide dismutase (SOD) has been recognized as a hopeful strategy to enhance the outcome of TBI ( Kobeissy et al, 2016 ). The function of SOD is to prevent the production of OH, thereby reducing brain damage ( Lv et al, 2016 ). To decrease the occurrence of ferroptosis, cells make use of antioxidants like GSH and NAC to remove an excess of oxidative free radicals.…”
Section: Ferroptosis and Mitochondrial Dysfunction In Tbimentioning
confidence: 99%
“…Previous studies have shown attempts to enhance the tolerance of the skin flaps to ischemia and congestion using different drug preparations 1 , 4 . Various agents have been stated to be beneficial in improving flap survival through inhibiting inflammation, getting rid of free radicals, improving angiogenesis, and/or increasing the microvascular network 1 .…”
Section: Introductionmentioning
confidence: 99%